Broccoli by-product extract as a functional ingredient: food application - David Q. Martínez; Francisco Lorca; Maria Dolores Fernández; Presentación García (Exploration of Foods and Foodomics, 2023)
Aim: Food production demand has been promoting an increase in the generation of agro-industrial waste. Food industry waste can contain compounds with added value that, if properly extracted and used, can be applied to the development of healthy foods (clean label), nutraceuticals, senior food, cosmetics, etc. The revaluation of by-products from the broccoli industry will make it possible to reduce the large volume of broccoli waste, reducing the cost of waste management and obtaining compounds of interest from them. The aim of this work is the extraction of compounds of interest by means of environmentally sustainable technologies and to characterize the freeze-dried broccoli extracts obtained in each green technology in terms of their characteristic compounds of interest and the study of antimicrobial and antioxidant capacity. Methods: The methods of extraction of compounds of interest from broccoli used in this research are environmentally sustainable technologies, using water as the extraction solvent, including aqueous extraction (AE), enzymatic extraction (EE), and ultrasound-assisted extraction (UAE). After extraction, the freeze-dried broccoli extracts obtained were characterized and the antimicrobial capacity was studied with Listeria and Salmonella strains and the antioxidant capacity was studied with Saccharomyces strains, thus determining which of the techniques is most effective for obtaining a freeze-dried broccoli extract with a high concentration of bioactive compounds. Results: As a result of the research, different products have been obtained from broccoli waste by means of three green extraction techniques, obtaining products with a high concentration of bioactive compounds with antioxidant and antimicrobial capacity against strains such as Listeria and Salmonella. Conclusions: The waste generated in the broccoli industry has been revalued to obtain high added value products using environmentally sustainable techniques. Due to their high concentration of bioactive compounds, these products are effective as functional products due to their antioxidant and antimicrobial capacity.